Stamp Duties as a Capital Gains Tax - Kennedy, Charles (Review of Economic Studies, 1955)
Journal Article Stamp Duties as a Capital Gains Tax Get access Charles Kennedy Charles Kennedy Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 3, 1955, Pages 241–244, https://doi.org/10.2307/2295730 Published: 01 December 1955